Identification of the bound and unbound lipids on the cell envelopes of Mycobacterium bovis - DANDAPAT, P; VERMA, RAVINDRA; VENKATESAN, K; SHARMA, V D; KATOCH, V M (The Indian Journal of Animal Sciences, 2014)
Sixteen Mycobacterium bovis isolates from bovine tissues and one reference strain M. bovis AN5 were investigated for differerrtoourrdandunoourrd upids. Forcomparison, other mycobacterial species induded in the study were M (uberculosis, M. bovis BCG and M. avium. The thin layer chromatographic (TLC) study indicated the absence of C-mycosides in all the M. bovis isolates while phosphatidyl inositol manno;ides (PIMs) was present in all M. bovis isolates, M. bovis BCG and M.tuberculosis as shown by TLC with the solvent chloroform-methanol-water (60:30:6, v/v x 1). The polar glycolipids were present in all the M. bovis isolates and M. tuberculosis showing seven bands with Rf value 0.62, 0.55, 0.44, 0.40,0.38,0.31 and 0.09 with the solvent n-propanol-watet-arnmonia(sp. gr. 0.89)(75:22:3, v/v x 1). The unidimensional TLC mycolates patterns of all M. bovis isolates including AN5 showed one spot corresponding to alpha-mycolate (as in M. tuberculosis) and the other spot being more diffuse in nature, covering the location of keto and methoxy mycolates.